Psychological Changes in Post Kidney Transplant Recipients: Phenomenology Study - Aisya Rahmadhanty; Yevri Zulfiqar; Devia Putri Lenggogeni; Meri Neherta; Emil Huriani; Fitri Mailani; Susmiati Susmiati (STIKep PPNI Jawa Barat, 2023)
Aims: Kidney transplantation can have a big impact on recipients, so they must be able to adapt to many changes, including psychological changes. Psychological changes are the most complained about by post- kidney transplant recipients. Psychological changes including feelings of anxiety and worry after kidney transplantation, these feelings arise due to post-transplant complications, feelings of guilt and fear of rejection, treatment regimens and uncertainty about the future. Therefore, recipients must be able to deal with psychological changes after kidney transplantation. Objective: To explore the psychological changes of post-kidney transplant recipients. Methods: A qualitative study using a phenomenological approach. This study was conducted on 6 participants who were undergone kidney transplantation. Purosive sampling was performed and data was collected through 35 to 60 min. Data collection in this study was carried out through in-depth interviews, audio recording and field notes. The data analysis technique uses the Collaizi method (1978). Result: This study obtained results including: psychological adaptation transitions and post-transplant anxiety control strategies. Conclusion: Kidney transplant provide better psychological changes if the recipients can implement strategies to control emotions. Therefore, it is important to have family, social and nurses support in controlling the psychological changes of post-kidney transplant recipients.